Quality by design for mRNA platform purification based on continuous oligo-dT chromatography - Jixin Qu; Adithya Nair; George W. Muir; Kate A. Loveday; Zidi Yang; Ehsan Nourafkan; Emma N. Welbourne; Mabrouka Maamra; Mark J. Dickman; Zoltán Kis (Elsevier, 2024)
Oligo-deoxythymidine (oligo-dT) ligand-based affinity chromatography is a robust method for purifying mRNA drug substances within the manufacturing process of mRNA-based products, including vaccines and therapeutics. However, the conventional batch mode of operation for oligo-dT chromatography has certain drawbacks that reduce the productivity of this process. Here, we report a new continuous oligo-dT chromatography process for the purification of in vitro transcribed mRNA, which reduces losses, improves the efficiency of oligo-dT resin use, and intensifies the chromatography process. Furthermore, the quality by design (QbD) framework was used to establish a design space for the newly developed method. The optimization of process parameters (PPs), including salt type, salt concentration, load flow rate and mRNA load concentration both in batch and the continuous mode, achieved a greater than 90% yield (mRNA recovery) along with greater than 95% mRNA integrity and greater than 99% purity. The productivity of continuous chromatography was estimated to be 5.75-fold higher, and the operating cost was estimated 15% lower, when compared with batch chromatography. Moreover, the QbD framework was further used to map the relationship between critical quality attributes and key performance indicators as a function of critical process parameters and critical material attributes.